Primary Giant Cell Tumor of Soft Tissue in The Female Breast - Dody Novrial; Muhammad Yamsun (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
A giant cell tumor of soft tissue (GCT-ST) is a rare tumor composed of mononuclear and osteoclast-like multinucleated giant cells. It is a low-grade malignant potential tumor morphologically analog to a giant cell tumor of bone. The superficial and deep soft tissue of extremities is the most frequent site of this tumor which is cured by complete or radical resection. GCT-ST as a primary tumor in the female Breast is exceedingly rare. Presentation of osteoclast-like multinucleated giant cells in the breast tumor has been described in association with the variant of breast carcinoma. We report a case of primary GCT-ST arising in the female Breast without a relationship with the epithelial component. To the best of our knowledge, this is the fifth such case report, and only the second one occurred in a female under 50 years.